Comparison of Anterior Chamber Depth Measured by IOLMaster and A-Scan Ultrasonography - Rabbani, Shafaq; Akram, Amjad; Yaqub, Amer; Ashraf, Ammara; Khan, Fatima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare anterior chamber depth measurements by ultrasound A-scan and IOLMaster, and evaluate interdevice agreement and interchangeability. Study Design: Cross-sectional study. Place and Duration of Study: Study was conducted on subjects attending preoperative cataract surgery clinic at Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Nov 2018 and Jan 2019. Methodology: Eighty subjects between 15 to 80 years of age were enrolled in the study. Biometric measurements of all subjects were carried out by a single investigator. The values obtained were compared using paired t-test, Pearson correlation and Bland-Altman analysis. Results: Sixty-two men and eighteen women were examined. Mean age was 61.3 ± 11.8 years. Mean anterior chamber depth was 3.25 ± 0.42 mm with A-scan and 3.25 ± 0.47 mm with IOLMaster. Mean difference was 0.007 ± 0.32 mm which was not statistically significant (p=0.852). The values were significantly correlated (r=0.749, p<0.001) and had no significant proportional bias (p=0.138). There was good agreement between the two devices for anterior chamber depth measurement. Anterior chamber depth was found to be positively correlated with axial length, negatively correlated with age and not correlated with intraocular pressure. Conclusion: Ultrasound A-scan and IOLMaster have good agreement in measuring anterior chamber depth. Any difference between them is not statistically significant and is unlikely to be clinically important.